The Applicable Dental Age Estimation Methods for Children and Adolescents in Indonesia - Arofi Kurniawan; An’nisaa Chusida; Nur Atika; Tito Krisna Gianosa; Mohammad Denis Solikhin; Mieke Sylvia Margaretha; Haryono Utomo; Maria Istiqomah Marini; Beta Novia Rizky; Beshlina Fitri Widayanti Roosyanto Prakoeswa; Aspalilah Alias; Anand Marya (HINDAWI, 2024)
Indexed by WOS/Scopus/ERA